Improvement of Selected Induction Culture Media on Callus Induction in Anther Culture of Anthurium and a Histological Study on its Callus Formation - Winarto, Budi; Mattjik, Nurhayati Ansori; Purwito, Agus; Marwoto, Budi (Jurnal Natur Indonesia, 2010)
Improvement of selected induction culture media on callus induction in anther culture of anthurium and a histologicalstudy on its callus formation were studied at the tissue culture laboratory of the Indonesian Ornamental CropsResearch Institute from February to October 2008. The objectives of the study were to optimize selected media forcallus formation, reveal cell origin of callus derived from anther culture and shoot formation process. Selectedmedia improved in the study were 1) MMS-TBN containing 0,5 mg/l TDZ, 1,0 mg/l BAP and 0,01 mg/l NAA (Winartomedium, WM) and 2) MMS III supplemented with 1,5 mg/l TDZ, 0,75 mg/l BAP and 0,02 mg/l NAA (Winarto andRachmawati medium, WRM). Improvement treatments were carried out by omission and application of 2,4-D in 0.5mg/l and reduction of medium strength of full, half, quarter, one eighth, one sixteenth, and zero strength. Afactorial experiment was arranged using a randomized complete block design with four replications. Results ofthis study indicated that the highest callus induction was clearly established in WRM. The medium stimulatedpotential growth of anther (PGA) up to 81% with 49% of percentage of anther regeneration (PAR) and 2.7 number ofcallus formed per replication (NCF). Significant improvement in callus formation was also recorded by reduction ofmedium strength of WRM to one eighth compared to others. The reduction induced PGA up to 58% with 29% of PARand 1.8 NCF. From histological studies it was well recognized that regenerated callus on half anthers cultured wasoriginated from middle layer cells of anther wall. The morphogenic response of anther wall cells caused primarilyon no androgenesis effect in microspore cells.